2012
DOI: 10.1523/jneurosci.1321-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin and Rod–Cone Photoreceptors Play Different Roles in Mediating Pupillary Light Responses during Exposure to Continuous Light in Humans

Abstract: In mammals, the pupillary light reflex is mediated by intrinsically photosensitive melanopsin-containing retinal ganglion cells that also receive input from rod-cone photoreceptors. To assess the relative contribution of melanopsin and rod-cone photoreceptors to the pupillary light reflex in humans, we compared pupillary light responses in normally-sighted individuals (n = 24) with a blind individual lacking rod-cone function. Here, we show that visual photoreceptors are required for normal pupillary responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
245
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(279 citation statements)
references
References 50 publications
27
245
2
5
Order By: Relevance
“…Underlying these NIF responses to light, traditional rod and cones photoreceptors are thought to be implicated in the fast and transient responses, whereas melanopsin is hypothesized to have a predominant effect on the sustainability and persistence of a response (33,34). To date, however, the integrative physiology light in a nonlinear fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying these NIF responses to light, traditional rod and cones photoreceptors are thought to be implicated in the fast and transient responses, whereas melanopsin is hypothesized to have a predominant effect on the sustainability and persistence of a response (33,34). To date, however, the integrative physiology light in a nonlinear fashion.…”
Section: Introductionmentioning
confidence: 99%
“…A fairly uniform distribution of the ipRGCs was reported by Moirn et al [25], Semo et al [37], and by Hughes et al [30] when all subtypes of ipRGCs have been taken into account. In addition, we should keep in mind that ipRGCs receive radiation stimuli not only intrinsically but also via the classical photoreceptors [3,30]. Hughes et al [30] have demonstrated the influence of both rods and cones on the spectral tuning of different subtypes of ipRGCs.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper the authors therefore refer to radiation instead of light. The ipRGCs transduce radiation received directly and via the rods and cones [3,4] to neural signals which are transmitted to different parts of the brain, e.g., the Supra-Chiasmatic Nuclei (SCN). The SCN regulates a set of endogenous physiological and behavioral (e.g., circadian) rhythms through its connection to the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on humans have demonstrated that both monochromatic short-wavelength light and blue-enriched polychromatic light are more effective than light at longer wavelengths at suppressing melatonin, [1][2][3] resetting the circadian clock, 4,5 enhancing alerting effects and cognitive function, 3,[6][7][8] and constricting the pupil. 9,10 These non-visual effects of light are primarily mediated by recently discovered intrinsically photosensitive retinal ganglion cells (ipRGCs). 11 These cells use melanopsin as a photopigment and, as a result, the ipRGCs are characterized by a spectral sensitivity curve that peaks in the short wavelength region around 490 nm, estimated in vivo, distinguished from the spectral sensitivity of rod and cone photoreceptors.…”
Section: Introductionmentioning
confidence: 99%